What Can One Learn from the Learning Style Inventory? - Freedman, Richard; Stumpf, Stephen A. (Academy of Management Journal, 1978)
The Learning Style Inventory is exemplary of instruments used in experiential learning about whose measurement properties little is known. Investigation of the instrument using graduate business students (n = 1,692) cast doubt about its practical usefulness, although some support for the underlying theory was demonstrated. This research suggests that greater care be taken with other instruments before they are applied in experiential learning.